The Modeling of the Production Process of High-Starch Corn Hybrids of Different Maturity Groups - Palamarchuk, Vitalii; Krychkovskyi, Vadym; Honcharuk, Inna; Telekalo, Nataliia (European Journal of Sustainable Development, 2021)
The article presents the results of mathematical modeling based on the construction and use of various images of the object, process or system. The research involves the study of the dependence of the level of productivity and valuable farming traits of corn hybrids in the form of mathematical models. Field research was carried out during 2011-2017 on the experimental fields of the Department of Crop Production, Breeding and Bioenergy Crops of Vinnytsia National Agrarian University, at the state enterprise “Research Farm “Kordelivske” of the Institute of Potato Production of the National Academy of Agrarian Sciences of Ukraine under conditions of the right-bank Forest-Steppe in accordance with the guidelines provided in “Methodology of Field Experiments in Corn”. The use of computer technology, in particular, cluster analysis, from our point of view, allows us to approach the difficult task of improving the efficiency of the correct choice of hybrids and technologies to obtain the maximum level of bioethanol yield per unit area of maize hybrids. An ecological-genetic model of quantitative traits was used to study the phenotypic productivity of corn hybrids and to establish the influence on the formation of their traits. The construction of the model is based on the hierarchy of manifestation of productivity traits in ontogenesis and the correspondence of their manifestation in organogenesis. The model consists of three modules of traits including the resulting one and double-component that reflect phenotypic implementation of the genetic formula. The resulting traits are those that have environmentally stable correlation and the highest total impact on the final resulting trait, namely, the yield. According to the results of researches of mathematical models of the influence of weather conditions on the formation of phenotypic productivity of corn hybrids of different maturity groups, both general biological regularities and group differences of trait formation have been established. Thus, the analysis of the differences between the groups of early and mid-early corn hybrids, in general reveals that their growth and development are affected to a relative extent by the amount of effective temperatures, amount of precipitation and HTC. In fact, the maturity groups studied differ insufficiently, and the main differences can be observed only in the variability of the traits studied or the closeness of their relationships with each other. However, mid hybrids respond somewhat differently to environmental factors, which allows to develop the elements of adaptive cultivation technology for each maturity group. Based on the results of cluster analysis, cluster dendrograms were created using the odd-numbered group method with the determination of Euclidean distances.